Do immigrants bring fiscal dividends? The case of Venezuelan immigration in Colombia - Oscar M. Valencia; Matilde Angarita; Juan Santaella; Marcela de Castro (Inter-American Development Bank (IDB), 2020)
This paper analyzes the effects of recent Venezuelan immigration to Colombia on the fiscal balance, the labor market, and economic growth. For this purpose, we built a dynamic general equilibrium model with a search and matching structure in the labor market. The higher fiscal spending to address immigration negatively impacts the government's budget in the short term, which is offset by higher output, consumption, and employment level, increasing the government's revenues mainly through indirect tax collection. The effect on the labor market is different for unskilled workers–whose higher supply generates a negative effect on wages and an increase in the unemployment rate–and skilled workers, who benefit from higher wages and lower unemployment. These changes in the labor market affect the government's revenue, resulting, in the long term, in positive fiscal dividends of migration.
Keywords: E62; J61; H 24; 330; fiscal policy; labor market; migration; unemployment